2006
DOI: 10.1089/apc.2006.20.36
|View full text |Cite
|
Sign up to set email alerts
|

The Disclosure Model versus a Developmental Illness Experience Model for Children and Adolescents Living with HIV/AIDS in São Paulo, Brazil

Abstract: Whether, how, and when children's HIV/AIDS diagnosis needs to be disclosed to them has received growing attention. This paper describes and conceptualizes how communication about HIV/AIDS influences disease knowledge and psychosocial development in a group of children and adolescents living with perinatally acquired HIV infection in an AIDS institution in São Paulo, Brazil. Data consist of the lived experience of 36 children ages 1 to 15 and was gathered through ethnographic research methodologies: participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
79
0
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(96 citation statements)
references
References 31 publications
11
79
0
6
Order By: Relevance
“…8 Here, similar to other studies, 12,32 children had a sense of social isolation and emotional distress, noted in messages to not touch other people's belongings and not share common household items, and unexpressed questions and concerns resulting perhaps from messages that worrying will make them sicker, but also possibly reflecting cultural norms around parent-child communication.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…8 Here, similar to other studies, 12,32 children had a sense of social isolation and emotional distress, noted in messages to not touch other people's belongings and not share common household items, and unexpressed questions and concerns resulting perhaps from messages that worrying will make them sicker, but also possibly reflecting cultural norms around parent-child communication.…”
Section: Discussionsupporting
confidence: 83%
“…A Brazilian study found that prolonged silence, poor adult-child communications, and self-discovery resulted in psychosocial distress, self-stigma and adherence problems among HIVpositive youth. 12 In other studies in clinical settings, health care providers play a large role in initiating disclosure with children, sometimes telling parents that it is time that the child should be told. 34,37 In this study's setting, providers were concerned with finding the best way to disclose to children, and were therefore not intervening with what they saw as the ''natural'' disclosure process currently taking place until more information was made available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although caregivers often delay disclosure till later age and adolescent, there is no evidence to suggest that disclosure negatively affects HIV-positive children. On the contrary, children who know their HIV diagnosis appear more likely to accept medical care and have higher self-esteem than those who are unaware of their diagnosis [10,14,28,29]. However, the few negative outcomes of disclosure documented, include the family's experience of stigma when children share their diagnosis with others, or an emotional burden for children when they are asked to keep HIV diagnosis a secret [28].…”
Section: Introductionmentioning
confidence: 99%
“…Disclosure as a process is supported in the literature, with studies describing disclosure models that stress an ongoing process and emphasize the caregiver's participation (AAP, 1999;Abadia-Barrero & LaRusso, 2006;Lesch et al, 2007). However, these models lack detailed descriptions of health information segmented to mirror cognitive development (Abadia-Barrero & LaRusso, 2006;Lesch et al, 2007). To promote an ongoing process-oriented disclosure for children with vertically transmitted HIV, we developed a framework structured according to Piaget's cognitive development theory that considers the developmental progression of illness understanding and allows reintegration of concepts.…”
mentioning
confidence: 99%